Comparison of Nutritional Content of Spinach (Amaranthus gangeticus L.) Cultivated Hydroponically and Non-Hydroponically - Fevria, Resti; Alicia Farma, Siska; Vauzia; Edwin, Edwin; Purnamasari, Devi (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2021)
The objectives of this study to determine the comparison of the nutritional content of spinach cultivated hydroponically and non-hydroponically, especially the content of Vitamin C. This research was conducted at the Wire House Biology Laboratory of Padang State University in May - July 2020. This research is a descriptive study. The analysis was carried out Spinach Nutrition. Hydroponic spinach samples were obtained from the Hydroponic Community of West Sumatra in Alai Padang, while the non-hydroponic samples were purchased at Pasar Raya Padang, the analysis of vitamin C content was carried out by the Spectrophotometric Method. From the research that has been done, it is found that the average content of hydroponic spinach vitamin C is 1.45 ppm and non-hydroponic 1.60 ppm. The conclusion of the research is that the content of Vitamin C in hydroponic cultivated spinach is lower than that of spinach cultivated non-hydroponically.